An optimization problem of packing identical circles into a multiply connected region. Part 2. A solution method and its realisation - Stoyan, Yu.G.; Chugay, A.M. (Проблемы машиностроения, 2011)
The paper deals with an optimization problem of packing identical circles into a multiply connected region whose frontier consists of arcs of circles and line segments. On the ground of the characteristics of a mathematical model a solution method is offered. The method consists of a combination of a method of generating starting points, a modification of the feasible directions method to search for local maxima and a modification of the decremental neighbourhood search method to find an approximation to a global maximum. Numerical examples are given. Рассматривается оптимизационная задача упаковки одинаковых кругов в многосвязную область, граница которой состоит из отрезков дуг окружностей и отрезков прямых. На основании свойств математической модели предлагается метод решения задачи. Метод предполагает комбинацию метода получения начальных точек, модифицированного метода возможных направлений для поиска локальных максимумов и модифицированного метода сужающихся окрестностей для поиска приближения к глобальному максимуму. Приводятся численные примеры. Розглядається оптимізаційна задача пакування однакових кіл у багатозв’язну область, границя якої складається з відрізків дуг околів та відрізків прямих. На підставі властивостей математичної моделі пропонується метод розв'язання задачі. Метод передбачає комбінацію методу одержання початкових точок, модифікованого методу можливих напрямів для пошуку локальних максимумів та модифікованого методу звужувальних околів для пошуку наближення до глобального максимуму. Наводяться числові приклади.